2022
DOI: 10.1007/s12010-021-03791-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking of Phytochemicals Targeting GFRs as Therapeutic Sites for Cancer: an In Silico Study

Abstract: Drug delivery in a safe manner is a major challenge in the drug development process. Growth factor receptors (GFRs) are known to have profound roles in the growth and progression of cancerous cells making these receptors a therapeutic target in the effective treatment of cancer. This work focused on exploring bioactive compounds that can target GFRs using in silico method. In this study, 50 bioactive compounds from different plant sources were screened as anticancer agent against GFRs using drug likeness param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Computer aided structure-based drug design approach provides a rapid and cost-effective strategy to explore anticancer potential of various natural compounds to develop lead candidates targeting cancer [49] , [50] , [51] . In the current study, 52 phytochemicals from O. indicum were investigated utilizing a structure-based drug design approach to determine their anticancer potential targeting Lactate Dehydrogenase A enzyme in silico.…”
Section: Discussionmentioning
confidence: 99%
“…Computer aided structure-based drug design approach provides a rapid and cost-effective strategy to explore anticancer potential of various natural compounds to develop lead candidates targeting cancer [49] , [50] , [51] . In the current study, 52 phytochemicals from O. indicum were investigated utilizing a structure-based drug design approach to determine their anticancer potential targeting Lactate Dehydrogenase A enzyme in silico.…”
Section: Discussionmentioning
confidence: 99%
“…One finding have noticed ajmalicine from R. serpentina was a potential inhibitor against VEGFR2. Some studies also reported that oleanolic acid, Panaxadiol, Ursolic acid, Withaferin A, Hecogenin were potential against GFRs [32] . In addition phytochemicals like Tricyclo (20.8.0.0 (7,16) triacontane, 1 (22), 7(16)‐diepoxy‐ (543764), Adaphostin, Obeticholic acid, Methylphenidate, HFB, Hypophyllanthin, Vitamin E, Clonitazene, Humulane‐1,6‐dien‐3‐ol from Nigella sativa L. seed extract [33] .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies also reported that oleanolic acid, Panaxadiol, Ursolic acid, Withaferin A, Hecogenin were potential against GFRs. [32] In addition phytochemicals like Tricyclo (20.8.0.0 (7,16) triacontane, 1 (22), 7(16)-diepoxy-(543764), Adaphostin, Obeticholic acid, Methylphenidate, HFB, Hypophyllanthin, Vitamin E, Clonitazene, Humulane-1,6-dien-3-ol from Nigella sativa L. seed extract. [33] Some studies also find that 1-Penten-3-ol, Ethyl benzoate, Methanol, α Cubenene, α Guinea, β Bourbonene, β-Cubebene, Eucalyptol were potential inhibitors against VEGFR.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…The identification of lead compounds based on their toxicological profiles was further analyzed for their bioavailability using the SwissADME web server ( http://www.swisstargetprediction.ch /) [ 23 ]. In order to analyze the lead compound's potential molecular targets, the SwissTargetPrediction web server was utilized; these predictions aid in understanding the compound’s pharmacological activities and their potential therapeutic applications [ 24 ].…”
Section: Methodsmentioning
confidence: 99%